Arrhythmic risk stratification in heart failure: Time for the next step?. Issue 2 (3rd February 2017) - Gatzoulis, Konstantinos A.; Sideris, Antonios; Kanoupakis, Emmanuel; Sideris, Skevos; Nikolaou, Nikolaos; Antoniou, Christos‐Konstantinos; Kolettis, Theofilos M.
Abstract : Background: Primary prevention of sudden cardiac death by means of implantable cardioverter‐defibrillators constitutes the holy grail of arrhythmology. However, current risk stratification algorithms lead to suboptimal outcomes, by both allocating ICDs to patients not deriving any meaningful survival benefit and withholding them from those erroneously considered as low‐risk for arrhythmic mortality. Methods: In the present review article we will attempt to present shortcomings of contemporary guidelines regarding sudden death prevention in ischemic and dilated cardiomyopathy patients and present available data suggesting encouraging results following implementation of multifactorial approaches, by using multiple modalities, both noninvasive and invasive. Invasive electrophysiological testing, namely programmed ventricular stimulation, will be discussed in greater length to highlight both its potential usefulness and currently ongoing multicenter studies aiming to provide evidence necessary to make the next step in sudden death risk stratification. Results: Promising findings have been reported by multiple study groups regarding novel strategies for both negative selection of low and positive selection of relatively preserved ejection fraction patients as candidates for ICD implantation. Conclusions: The era of ejection fraction as the sole risk stratifier for arrhythmic risk in heart failure appears to be drawing to an end, especially if current underway large studies validate previous findings.